MicroRNA-499a in heart diseases: prospects for use in diagnostics. A review - Maria V. Pisklova; Natalia M. Baulina; Ivan S. Kiselev; Olga O. Favorova (Терапевтический архив)
Cardiac-specific (or myomiR) miRNA-499a (miR-499a) is a small (21–22 bp) non-coding RNA that is involved in the regulation of cardiac function both under normal and in various pathological conditions. Every year new studies expand the range of known biological processes that are regulated by miR-499a in the heart. In acute and chronic cardiovascular diseases accompanied by cardiomyocyte damage, miR-499a enters the bloodstream and can circulate there for a long time. At the same time, it is detected in plasma significantly earlier than traditional protein biomarkers, which makes it a new promising biomarker for early diagnosis and prognosis of heart diseases. This review describes the functions of human miR-499a and its involvement in the development of heart diseases. The data indicating the high diagnostic value of this miRNA in blood are presented.